Media Education and the New Evangelization. Part One: Media Components and Challenges - Chmielewski, Mirosław (Verbum Vitae, 2020)
This article represents the first instalment of a two-part study on the relationship between media education and the new evangelization. The author puts forward a claim that pursuing the new evangelization in the Church demands the media education of the evangelizers and their cooperation with leaders in media education. Proving this thesis advances via three stages: (1) Outlining selected components of the media context of the new evangelization, in light of selected theses from the Church Magisterium; (2) Discussing selected challenges for both media education and the new evangelization; and (3) Presenting selected postulates and educational proposals for media literacy formation and the new evangelization. This last part outlines five media components of the new evangelization, along with three main challenges for both media and the new evangelization, stemming from their interrelationship. The main research methods used in this article are: the Magisterial method, sub ratione Dei, and comparative synthesis.